HLA DQA1’İN PCR ÜRÜNLERİNİN KAPİLLER JEL ELEKTROFOREZİ - YILMAZ, Sevgi; CENGİZ, Salih (Cerrahpaşa Medical Journal, 2019)
Background.- HLA DQA 1 loci are highly informative polymorphic loci that are gaining popularity for identity testing. HLA DQA 1 system easy to work with, fast and reliable. This loci with PCR technique is a very promising tool for genetic investigations in both paternity and crime cases. Design.- Human genomic DNA was extracted by Chelex(r) 100 procedure. The amplification of HLA DQA 1 locus was performed by single locus PCR reaction in the case of HLA DQA 1 locus according to the manufacturer's recommendations using the Perkin Elmer AmpliType DQA 1 PCR Amplification Typing Kits. The electrophoresis of PCR products of HLA DQA 1 are carried out on agarose gel. Results.- It was shown from the obtained bands that the DNA is amplified. Hybridization is made from the PCR products by Perkin Elmer AmpliType DQA 1 PCR Amplification Typing Kits and that typed as 2,3 as a result and this allele was compared with the Capillary electrophoreograms. Conclusion.- In this study, Capillary gel electrophoresis (CGE) was performed on PCR products of HLA DQA 1 due to its advantages are ultraresolution, ultralow sample , extremely high efficiency, rapid separation time, easy quantitation and amenability to automation.